Large-scale synchrony, global interdependence and contagion - Eric J. Friedman; Simon Johnson; A. S. Landsberg (Rutgers University, Department of Economics, 2001)
We construct a simple firm-based model of global interdependence. We show how extremely strong statistical correlations can naturally develop between countries even if the interconnections between those countries remain very weak. Potential policy implications of this result are also discussed.
Keywords: F40; 330; large scale synchrony; Wirtschaftskrise; Internationaler Preiszusammenhang; Schock; Unternehmensnetzwerk; Theorie